2022
DOI: 10.1177/0044118x221116906
|View full text |Cite
|
Sign up to set email alerts
|

Popularity Goals and Bullying Behaviors Among Chinese Adolescents: The Moderating Roles of Popularity Status and Cognitive Empathy

Abstract: Bullying is a goal-directed behavior that has long been in the spotlight of worldwide school mental health programs and research. However, the role of popularity goals in bullying and its potential mechanisms are unclear for adolescents in a non-Western cultural context. Based on 333 Chinese adolescents (52% female), the current study was the first to explore the potential moderating roles of popularity status and cognitive empathy in the association between popularity goals and early Chinese adolescents’ bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For example, in England, bullying and harassment are estimated to cost taxpayers approximately $2.281 billion annually (9). Following previous studies (11,12), this study distinguishes between two different kinds of bystander behavior when witnessing bullying at school: active defending behaviors, which are behaviors that may stop bullying or protect victims from bullies (e.g., intervening to stop the bullying, asking for an adult or teacher's help), and passive bystanding behaviors, which are behaviors that "withdraw from the scene, deny any bullying is going on, or remain as a silent audience" to bullying (11). Numerous studies have shown that the behavior of bystanders during bullying can either reduce bullies' harm (active defending behaviors in this study, such as stopping bullies or calling adults for help) or aggravate harm (passive bystanding behaviors, such as minding their own business or avoiding bullying incidents) (11,13,14).…”
Section: Introductionmentioning
confidence: 93%
“…For example, in England, bullying and harassment are estimated to cost taxpayers approximately $2.281 billion annually (9). Following previous studies (11,12), this study distinguishes between two different kinds of bystander behavior when witnessing bullying at school: active defending behaviors, which are behaviors that may stop bullying or protect victims from bullies (e.g., intervening to stop the bullying, asking for an adult or teacher's help), and passive bystanding behaviors, which are behaviors that "withdraw from the scene, deny any bullying is going on, or remain as a silent audience" to bullying (11). Numerous studies have shown that the behavior of bystanders during bullying can either reduce bullies' harm (active defending behaviors in this study, such as stopping bullies or calling adults for help) or aggravate harm (passive bystanding behaviors, such as minding their own business or avoiding bullying incidents) (11,13,14).…”
Section: Introductionmentioning
confidence: 93%
“…Second, Chinese culture places high value on interpersonal interdependence and the maintenance of harmony with others. Therefore, being bullied by peers is a more culturally threatening event for Chinese adolescents (Tong et al, 2022). It is ideal to explore the specificity of the role of being bullied in a collectivist culture.…”
Section: The Chinese Social Culture Contextmentioning
confidence: 99%
“…To deepen our understanding of bullying victimization, it is necessary to examine the outcomes of bullying victimization in schools from a non-Western context. Chinese societies are deeply influenced by collectivistic and Confucian philosophy, which stresses interpersonal harmony and interdependence (Lim, 2009;Bond, 2010;Tom et al, 2010;Tong et al, 2022). Obtaining peer group approval and inclusion is especially vital for Chinese adolescents' social lives (Lu et al, 2018;Tong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation